The independent adverse prognostic significance of 1q21 gain/amplification in newly diagnosed multiple myeloma patients - You, Hongying; Jin, Song; Wu, Chunxiao; Wang, Qingqing; Yan, Shuang; Yao, Weiqin; Shi, Xiaolan; Shang, Jingjing; Yan, Lingzhi; Yao, Ying; Wang, Jing; Wang, Panfeng; et al. (Frontiers in Oncology, 2022)
Objective: 1q21 gain/amplification (1q21+) is a common abnormal karyotype in multiple myeloma, and its proportion in Chinese patients is much higher. If 1q21+ is included as one of the poor prognostic factors, it will greatly increase the proportion of high-risk patients in newly diagnosed multiple myelome (NDMM) patients. Therefore, the poor prognostic significance of 1q21+ is still controversial. This study mainly analyzed the clinical characteristics, treatment response and prognostic significance of 1q21+ in NDMM patients. Methods: 248 NDMM patients admitted in The First Affiliated Hospital of Soochow University from September 01, 2018 to August 31, 2021 of a VRD registration study, were retrospectively analyzed. 135 cases (54.4%) had 1q21+ by CD38-sorted fluorescence in situ hybridization (FISH). The clinical characteristics, treatment response and prognosis of the general population and subgroups were analyzed, among which 153 patients were compared for the involved genes by CytoScan. Results: Compared with negative patients, 1q21+ patients were more likely to have anemia, hypoalbuminemia, renal insufficiency, high lactate dehydrogenase and high proportion of R-ISS-III stage. The patients with 1q21+ involving CKS1B detected by Cytoscan had a higher proportion of complex karyotypes and abnormal CNVs, and all at middle-risk or high-risk groups defined by Prognostic Index. Multivariate analysis showed that 1q21+ was an independent adverse prognostic factor (PFS HR=2.358, 95%CI 1.286-4.324, P=0.006; OS HR=2.598, 95%CI 1.050-6.425, P=0.039). 1q21+ subgroup had an inferior outcome (PFS P=0.0133, OS P=0.0293). Furthermore 1q21 amplification had a shorter PFS than 1q21 gain (24 months vs not reached, P=0.0403), but the OS difference was not clinically significant. The proportion of 1q had no effects on prognosis. In addition, 1q21+ in main clone rather than subclone was an adverse factor affecting the prognosis (PFS P=0.0172, OS P=0.1260). Autologous stem cell transplantation can effectively improve the survival of 1q21+ patients (P<0.05). Conclusion: Patients with 1q21+ have clinically significant end-stage organ damage and higher tumor burden, more likely to combine 13q14-, t(4;14), 1p32- and other cytogenetic abnormalities. 1q21+ is an independent high-risk cytogenetic factor for poor prognosis in NDMM patients, of which 4 or more copy numbers and main clone position significantly associated with prognosis results.